Ženy v pozadí, či jako aktivní hospodářky? Podíl šlechtičen na hospodaření a správě raně novověkého velkostatku - Marie Ryantová (Theatrum Historiae)
The contribution looks at the share of women in the economic activities and management of the manor of the early modern nobility, which became increasingly important with the increase in the activities and workload of their husbands. Simultaneously, the contribution raises the question of what being an active landowner meant.